PENGARUH FREKUENSI PEMBERIAN PAKAN YANG BERBEDA TERHADAP PERTUMBUHAN MUTLAK UDANG VANAME (Litopenaeus vannamei) UKURAN PL 6 (30 HARI) - Medi Hartono; Indra Wirawan; Muhajir Muhajir (Universitas Mataram, 2026)
Whiteleg shrimp farming is a significant and leading aquaculture industry in Indonesia. One of the main challenges faced by shrimp farmers is the high cost of feed. Appropriate feeding frequency is crucial to improve feed efficiency, supporting growth, FCR, and survival rates of whiteleg shrimp. This article aims to determine the Effect of Different Feeding Frequencies on the Absolute Growth of Pacific White Shrimp (Litopenaeus vannamei) at the PL 6 stage (30 days old) and their health status, as well as to identify the optimal feeding frequency for achieving peak absolute weight gain and shrimp health. The methodology employed in this study is experimental, with data collected through direct observational methods. The experimental design used is a Completely Randomized Design (CRD) consisting of 4 treatments and 6 replications of varying feeding frequencies: Treatment (A): 3 times per day. Treatment (B): 4 times per day. Treatment (C): 5 times per day. Treatment (D): 6 times per day. The results of this study indicate that the frequency of feeding results in a difference in the growth of vaname shrimp body weight with treatment B with the highest value which will result in profits in vaname shrimp cultivation production.